2010
DOI: 10.1016/j.neuroscience.2010.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cerebellar granule cell turning by alcohol

Abstract: Ectopic neurons are often found in the brains of fetal alcohol spectrum disorders (FASD) and fetal alcohol syndrome (FAS) patients, suggesting that alcohol exposure impairs neuronal cell migration. Although it has been reported that alcohol decreases the speed of neuronal cell migration, little is known about whether alcohol also affects the turning of neurons. Here we show that ethanol exposure inhibits the turning of cerebellar granule cells in vivo and in vitro. First, in vivo studies using P10 mice demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 105 publications
(186 reference statements)
0
16
0
Order By: Relevance
“…Because we observed a decreased expression of the granule cell progenitor marker Atonal1a at early ages, as well as a delay in its expression, it is possible that ethanol exposure during zebrafish CNS development is both decreasing the number of granule cell progenitors, as well as causing a delay in the differentiation of granule cells, as was observed with GABAergic Purkinje cells. It is also possible that migration of Atonal1a-positive granule cell progenitors to the cerebellum is impaired by ethanol exposure, and studies in rodents show that ethanol exposure perturbs granule cell migration from the external granule cell layer (Gonzalez-Burgos and Alejandre-Gomez, 1995; Kumada et al, 2010;Luo, 2010). In preliminary studies, we have analyzed BrdU incorporation by rhombic lip cells, and these data suggest that ethanol exposure may be decreasing cell proliferation in the rhombic lip (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Because we observed a decreased expression of the granule cell progenitor marker Atonal1a at early ages, as well as a delay in its expression, it is possible that ethanol exposure during zebrafish CNS development is both decreasing the number of granule cell progenitors, as well as causing a delay in the differentiation of granule cells, as was observed with GABAergic Purkinje cells. It is also possible that migration of Atonal1a-positive granule cell progenitors to the cerebellum is impaired by ethanol exposure, and studies in rodents show that ethanol exposure perturbs granule cell migration from the external granule cell layer (Gonzalez-Burgos and Alejandre-Gomez, 1995; Kumada et al, 2010;Luo, 2010). In preliminary studies, we have analyzed BrdU incorporation by rhombic lip cells, and these data suggest that ethanol exposure may be decreasing cell proliferation in the rhombic lip (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of rats through gestation and weaning (voluntary drinking; BAL = 0.07 g/dl) increased soma size and dendritic length in cerebellar granule cells, and delayed maturation of Bergmann glia [47]. Moreover, a recent study reported alterations in cerebellar granule cell migration in a mouse model of ethanol exposure during the 3 rd trimester-equivalent (1 g/kg intraperitoneal injection at P10; BAL = 0.07 g/dl) [48]. In addition, 3 rd trimester-equivalent exposure (1-2 g/kg/day P2-11; intragastric intubation; BAL = 0.05-0.15 g/dl) impaired eyeblink conditioning in adult rats, which could be related to alterations in deep cerebellar nuclear neurons [49].…”
Section: Cerebellummentioning
confidence: 99%
“…Voluntary drinking has also been used to expose monkeys to ethanol at different stages of pregnancy [62]. B) To model human exposure during the 3 rd trimester, rat pups and dams were exposed via ethanol vapor inhalation chambers [35, 55] or C) pups via intraperitoneal or subcutaneous ethanol injections [48, 64]. …”
Section: Box 1 What Is Moderate Drinking?mentioning
confidence: 99%
“…During the last 2 decades, real-time observation of cell movement demonstrated that granule cells display a distinct mode, tempo, and rate of migration as they traverse different cortical layers (13)(14)(15)(16)(17). It became apparent that granule cell migration is controlled by the orchestrated activity of multiple molecular events at the right time and right place, including pathway selection, activation of specific receptors and channels, and assembly and disassembly of cytoskeletal components (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%